Psoralea corylifolia Linn.—“Kushtanashini” - P. S., Khushboo; V. M., Jadhav; V. J., Kadam; N. S., Sathe (Pharmacognosy Reviews, 2010)
Plants have been the basis of many traditional medicines throughout the world for thousands of years and continue to provide new remedies to mankind. Plants have been one of the important sources of medicines since the beginning of human civilization. The recent resurgence of plant remedies resulted from several factors, such as effectiveness of plant medicines and lesser side effects compared with modern medicines. Psoralea corylifolia, commonly known as babchi, is a popular herb, which has since long been used in traditional Ayurvedic and Chinese medicine for its magical effects to cure various skin diseases. This plant is also pharmacologically studied for its chemoprotective, antioxidant, antimicrobial, and antiinfl ammatory properties. This review attempts to highlight the available literature on P. corylifolia with respect to its ethnobotany, pharmacognostic characteristics, traditional uses, chemical constituents, and summary of its various pharmacologic activities and clinical effects. Other aspects, such as toxicology and precautions are also discussed. This will be helpful to create interest toward babchi and may be useful in developing new formulations with more therapeutic and economical value.
Keywords: Babchi; leukoderma; Psoralea corylifolia; psoriasis; psoralen